2009
DOI: 10.1143/jpsj.78.054702
|View full text |Cite
|
Sign up to set email alerts
|

Quadrupole Susceptibility and Elastic Softening due to a Vacancy in Silicon Crystal

Abstract: We investigate the electronic states around a single vacancy in silicon crystal by using the Green's function approach. The triply degenerate vacancy states within the band gap are found to be extended over a large distance ∼ 20Å from the vacancy site and contribute to the reciprocal temperature dependence of the quadrupole susceptibility resulting in the elastic softening at low temperture. The Curie constant of the quadrupole susceptibility for the trigonal mode (Oyz, Ozx, Oxy) is largely enhanced as compare… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…Such phenomenon, which is observed in low-temperature ultrasonic measurements, attracts much attention because the density of the vacancies in silicon wafers can be estimated from the behavior of the elastic softening [1]. Several authors have studied this phenomenon theoretically by using a kind of model that includes adjustable or phenomenological parameters in the Hamiltonian [2][3][4][5][6][7]. It is pointed out that the spin-orbit interaction, which is one of the relativistic effects, plays an important role as well as the Zeeman effect [2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such phenomenon, which is observed in low-temperature ultrasonic measurements, attracts much attention because the density of the vacancies in silicon wafers can be estimated from the behavior of the elastic softening [1]. Several authors have studied this phenomenon theoretically by using a kind of model that includes adjustable or phenomenological parameters in the Hamiltonian [2][3][4][5][6][7]. It is pointed out that the spin-orbit interaction, which is one of the relativistic effects, plays an important role as well as the Zeeman effect [2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have studied this phenomenon theoretically by using a kind of model that includes adjustable or phenomenological parameters in the Hamiltonian [2][3][4][5][6][7]. It is pointed out that the spin-orbit interaction, which is one of the relativistic effects, plays an important role as well as the Zeeman effect [2][3][4][5][6][7]. In these works, an unusual (negative) value is used for the spin-orbit coupling constant in order to explain the above phenomenon, however, the validity of this approach is open to challenge [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[16,17] The theoretical analysis of the vacancy orbital in silicon gives enhanced electric quadrupoles due to an extended radius, which is consistent with the large quadrupole-strain interaction determined by the ultrasonic experiments. [18,19] The deformation energy of 14 eV for the vacancy orbital due to the dangling bonds may be comparable to deformation potential about 15 eV for the electron band due to the host valence bonding in silicon. [20,21] …”
Section: Softening Of Elastic Constantsmentioning
confidence: 95%
“…It is also reported that the elastic softening is suppressed by an external magnetic field in the boron-doped silicon [1]. Several papers concerning such phenomena have been published so far, and it is pointed out that the spin-orbit interaction plays an important role on them as well as the Zeeman effect [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%